PENERAPAN MODEL PEMBEALAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN NARASI SISWA KELAS V SDN 21 TENGGAYUN KECAMATAN BUKIT BATU - Azwin Anadayani; otang Kurniaman; zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the low ability students' Reading Comprehension narrative with an average value of data beginning at 50.83. Formulation of the problem in this study is whether the model pmbelajaran cooperative Cooperative Integrated Reading and Composition (CIRC) can Increase Increase Reading Comprehension Ability Narrative Student Class IV SD Negeri 21 Tenggayun Bukit Batusubdistrict? The research objective is to Improve Reading Comprehension Ability Narrative Student Class IV SD Negeri 21 Tenggayun Bukit Batusubdistrict with the implementation of cooperative learning model Cooperative Integrated Reading and Composition (CIRC). This design is a class action (PTK) which performed a total of two cycles, each cycle consisting of two meetings and one daily tests. From this research, the ability of the student Narrative Reading Comprehension daily test I in the first cycle by an average of 70.00, the second daily test on the second cycle average of 80.00 The results of the data analysis activities of teachers of the first cycle of meetings 1 of 58 % category quite at a meeting 2 66.7% good category, the second cycle 1 meeting kategoi 75% good and 83% 2nd meeting, student activities at the meeting amounted to 58.3% of category 1 sufficient, 2 meeting by 70.8% both categories, the second cycle 1 meeting by 75% and meeting the good category 2 by 83.3% very good category. From these results it can be concluded that the Application of Cooperative Learning Model Cooperative Integated Reading and Composition (CIRC) can Improve Reading Comprehension Ability Narrative Student Class IV SD Negeri 21 Tenggayun Bukit Batusubdistrict.Keywords : Cooperative Learning Model Cooperative Integrated Reading and Composition (CIRC), Reading Comprehension Narrative.